Perceived causal networks created using structured interviews: feasibility and reliability - Kaariniemi, Ella; Bosund, V.; Reichert, Julian; Bjureberg, J.; Klintwall, L. (Cognitive behaviour therapy, 2025)
The network approach to psychopathology postulates that it is more helpful to think of psychiatric problems to be caused by each other, rather than by underlying diseases. Personalized networks can be created using questionnaires asking participants about their perceptions of the causal links between symptoms, which is time-efficient but has shown low test-retest reliability. The present study explores whether perceptions of causal links can instead be assessed using interviews. The study investigates the feasibility, acceptability and test-retest reliability of such an interview format. 21 adolescents were interviewed twice within one week. Results showed an average test-retest reliability for node centrality of rs = .703 (SD = .148), and for causal links rs = .533 (SD = .198). A majority of participating adolescents rated the interview as easy to understand. On a group level, the node both most central and frequent was negative emotions. Future studies should evaluate the clinical utility of networks created in interviews, both in terms of face-validity and to guide clinicians in treatment choices.